INDEBTEDNESS OF FINANCIALLY VULNERABLE HOUSEHOLDS: WHAT DO SOCIAL WORKERS DO? - Engelbrecht, Lambert (Social Work/Maatskaplike Werk, 2009)
Household debt in South Africa has grown significantly relative to income over the past twenty years under the guise of financial liberalisation (FinMark Trust, 2007). Currently households spend approximately 60c to 70c of every rand of their income on repayment of debt (Gous, 2008; Van Rooyen, 2008a). During the past decade the disposable income, financial assets and net prosperity of households have therefore not accrued to the same extent as their debt obligations. For this reason households’ savings are urgently needed to contribute to a lessening of the country’s current account deficit in order to sustain economic growth and job creation (Van Tonder, 2008). On the macro level, economic growth and job creation form part of the ideal underpinning the social development philosophy in South Africa. This ideal is to combine social welfare assistance with developmental strategies, thereby promoting both economic and social development in order to strengthen people’s capacity to enhance their social and economic inclusion and alleviate poverty (Patel, 2005:118). Social work, as a profession within the social development paradigm, is primarily focused on the poorest of the poor households (Department of Social Development, 2006). In the context of a relative poverty line, set in relation to changing standards of living (Statistics South Africa, 2007), a poor household is to be understood when the household’s condition of poverty endures over a period of time, when the household has an inability or lack of opportunity to improve its circumstances over time, or to sustain itself through difficult times (Aliber, 2001:2). Research (Collins, 2007; Rand, 2004) has shown that poor households have the highest debt to income ratio. For this reason social work intervention focusing on household debt is also essential on the micro level within the social development paradigm in order to reduce households’ financial vulnerability (Engelbrecht, 2008a).